2011
DOI: 10.5194/amt-4-215-2011
|View full text |Cite
|
Sign up to set email alerts
|

MAMAP – a new spectrometer system for column-averaged methane and carbon dioxide observations from aircraft: instrument description and performance analysis

Abstract: Abstract. Carbon dioxide (CO 2 ) and Methane (CH 4 ) are the two most important anthropogenic greenhouse gases. CH 4 is furthermore one of the most potent present and future contributors to global warming because of its large global warming potential (GWP). Our knowledge of CH 4 and CO 2 source strengths is based primarily on bottom-up scaling of sparse in-situ local point measurements of emissions and upscaling of emission factor estimates or top-down modeling incorporating data from surface networks and more… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
75
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 88 publications
(79 citation statements)
references
References 44 publications
3
75
0
1
Order By: Relevance
“…Alternatively, atmospheric measurements potentially provide a constraint on the minimum wetland fraction that should be represented in a wetland product. Gerilowski et al (2011) are developing a successor to the SCIAMACHY instrument -the methane mapper (MAMAP). They considered a number of potential sources, including wetlands, which could be monitored by the MAMAP instrument.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, atmospheric measurements potentially provide a constraint on the minimum wetland fraction that should be represented in a wetland product. Gerilowski et al (2011) are developing a successor to the SCIAMACHY instrument -the methane mapper (MAMAP). They considered a number of potential sources, including wetlands, which could be monitored by the MAMAP instrument.…”
Section: Discussionmentioning
confidence: 99%
“…Heue et al, 2008;Gerilowski et al, 2011;Beirle et al, 2011;Merlaud et al, 2012;General et al, 2014).…”
Section: Introductionunclassified
“…They concluded that with an adequate spectral calibration approach, the impact of the inhomogeneous slit illumination on spectral calibration can be minimised. Gerilowski et al (2011) demonstrated with an airborne spectrometer that scene inhomogeneities on scales of about 50 m result in enhanced noise contributions even under cloud free conditions. Nevertheless, there is to the authors' knowledge no analysis of impact of scene inhomogeneity on the trace gas concentrations errors published so far.…”
Section: Introductionmentioning
confidence: 99%